2017
DOI: 10.1371/journal.pone.0173725
|View full text |Cite
|
Sign up to set email alerts
|

Tetrandrine inhibits migration and invasion of human renal cell carcinoma by regulating Akt/NF-κB/MMP-9 signaling

Abstract: Renal cell carcinoma (RCC) is known as one of the most lethal malignancies in the urological system because of its high incidence of metastasis. Tetrandrine (Tet), a traditional Chinese herbal medicine, exerts a potent anti-cancer effect in a variety of cancer cells. However, the anti-metastatic effect of Tet and its possible mechanism in RCC is still unclear. The present study revealed that Tet significantly suppressed the migration and invasion of RCC 786-O and 769-P cells in vitro. Mechanistically, the prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 30 publications
1
22
1
Order By: Relevance
“…[40][41][42] In this study, RNA interference experiment was carried out to clarify whether MMP-2 and MMP-9 was associated with the cell metastasis in Hep3B cells. We have observed that knockdown of MMP-2 and MMP-9 could inhibit the cell migration and invasion ability in Hep3B cells.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42] In this study, RNA interference experiment was carried out to clarify whether MMP-2 and MMP-9 was associated with the cell metastasis in Hep3B cells. We have observed that knockdown of MMP-2 and MMP-9 could inhibit the cell migration and invasion ability in Hep3B cells.…”
Section: Discussionmentioning
confidence: 99%
“…NF‐κB is a complex family, thus, further investigations are needed in the future. The epithelial‐mesenchymal transition (EMT) had been shown to get cells to obtain strong capability of motility for leading cells to metastasis to the distant regions . During EMT, epithelial phenotype transforms into mesenchymal phenotype .…”
Section: Discussionmentioning
confidence: 99%
“…TET inhibits Wnt/β‐catenin pathway and decreases metastatic tumor antigen 1 (MTA1) expression to modulate hepatocellular carcinoma cell metastasis . TET inhibited migration and invasion of renal cell carcinoma partially by regulating Akt/NF‐κB/MMP‐9 signaling pathway and suppresses metastatic phenotype of prostate cancer cells by regulating Akt/mTOR/MMP‐9 signaling pathway . However, there is no available information to show TET affect cell migration and invasion on human brain Glioblastoma multiforme 8401 cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Tetrandrine has broad-spectrum antitumor effects (Bhagya and Chandrashekar 2018;Liu 2017;Liu et al 2016) in many types of cancer cells, including human liver cancer (Zhang et al 2018a;Yu and Ho 2013), osteosarcoma Lu et al 2017), oral cancer (Lien et al 2017;Huang et al 2013), colon carcinoma (Meng et al 2004;Li et al 2019), gastric cancer (Bai et al 2018;Qin et al 2013), brain glioblastoma multiforme GBM 8401 cancer (Jiang et al 2019) and lung carcinoma (Chow et al 2018;Cho et al 2009). It also exhibits antineoplastic activity against gallbladder carcinoma (Zhu et al 2014), thyroid carcinoma B-CPAP cells ), prostatic carcinoma PC3 cells (Lan et al 2018), esophageal cancer , breast cancer (Guo and Pei 2019), pancreatic cancer (Singh et al 2018), nasopharyngeal carcinoma (Lin et al 2016(Lin et al , 2017b, acute megakaryoblastic leukemia (Liu et al 2017c), cervical cancer (Zhang et al 2018b) and renal carcinoma (Chen et al 2014(Chen et al , 2017a cells. Although tetrandrine exhibited broad anti-tumor effects, a number of these studies lacked positive controls or anti-tumor evaluation of tetrandrine in vivo.…”
Section: Anti-inflammatory Effectsmentioning
confidence: 99%
“…Reversal of multidrug resistance is an additional important mechanism of the anticancer effects of tetrandine (9) and fangchinoline (10). These two compounds are effective in overcoming multidrug resistance in a variety of tumor cells in a synergistic manner via modulation of P-glycoprotein (Choi et al 1998;Sun and Wink 2014;Lu et al 2017), multidrug resistance-associated protein 1 , multidrug efflux transporters (Yao et al 2017), Akt/NF-jB/matrix metalloprotein (MMP)-9 (Chen et al 2017a) and b-catenin expression (Zhang et al 2017b). Tetrandine has also been shown to enhance radiation sensitization for human nasopharyngeal carcinoma cells by modulating phosphorylated histone H2AX (c-H2AX), phosphorylated CDC25C, phosphorylated cyclin-dependent kinase 1 (p-CDK1) and CDK1 (Ding et al 2008;Wang et al 2017c).…”
Section: Anti-inflammatory Effectsmentioning
confidence: 99%